PENGARUH CITRA MERK, MOTIVASI DAN KEPUTUSAN PEMBELIAN TERHADAP KEPUASAN KONSUMEN GENERASI MILENIAL PADA MARKETPLACE (studi kasus generasi milenial dalam berbelanja online di market place: Tokopedia, Shopee, Bukalapak, Lazada) - Nurul Giswi Karomah; Ria Estiana; Rahmi Rosita; Ari Susanti (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2022)
This research was conducted to find out how the influence of brand image, motivation, and purchasing decisions on Millennial Generation Consumer Satisfaction on E-commerce buyers at Shopee and Lazada. The population in this study were all Shopee, LAZADA, Bukalapak, and Tokopedia e-commerce buyers and the number of samples used was 140 people. The analytical tool used is path analysis. The method used is a quantitative method. The sampling technique used is incidental. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. Based on the results of calculations using Part Analysis, Brand Image has a positive and significant effect on Purchase Decisions in the marketplace. This is obtained from a significance value of 0.000 <0.05. Purchase motivation has a positive and significant effect on purchasing decisions in the marketplace. This is obtained from a significance value of 0.001 <0.05, which means that there is an influence of Purchase Motivation on Purchase Decisions in the marketplace. The direct effect given by the brand image on consumer satisfaction is 0.012. The direct effect given by the purchase motivation on consumer satisfaction is 0.599.